Faktor Faktor Yang Mempengaruhi Kinerja Sumber Daya Manusia di SMK Ignatius Semarang - Riyono Riyono; Hani Krisnawati; Y. Sutomo; Sukirman Sukirman; Kasidi Kasidi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Human resource performance is one of the main factors for the Company. With the existence of factors that influence the performance of human resources, it is hoped that there will be improvements in the performance of human resources in a company so that better conditions and environments can be created. In connection with this, it becomes interesting to carry out community service activities with the aim of providing students with insight into the world of work. Implementation is carried out by means of lectures and discussions with students. The results of this service activity: participants appeared to be highly enthusiastic, because they felt they had benefited from the resource person's presentation by asking questions and discussing.